13C Breath Tests Are Feasible in Patients With Extracorporeal Membrane Oxygenation Devices. Issue 7 (3rd November 2015) - Bednarsch, Jan; Menk, Mario; Malinowski, Maciej; Weber‐Carstens, Steffen; Pratschke, Johann; Stockmann, Martin
Abstract: Temporary extracorporeal membrane oxygenation (ECMO) has been established as an essential part of therapy in patients with pulmonary or cardiac failure. As physiological gaseous exchange is artificially altered in this patient group, it is debatable whether a 13 C‐breath test can be carried out. In this proof of technical feasibility report, we assess the viability of the 13 C‐breath test LiMAx (maximum liver function capacity) in patients on ECMO therapy. All breath probes for the test device were obtained directly via the membrane oxygenator. Data of four patients receiving liver function assessment with the 13 C‐breath test LiMAx while having ECMO therapy were analyzed. All results were compared with validated scenarios of the testing procedures. The LiMAx test could successfully be carried out in every case without changing ECMO settings. Clinical course of the patients ranging from multiorgan failure to no sign of liver insufficiency was in accordance with the results of the LiMAx liver function test. The 13 C‐breath test is technically feasible in the context of ECMO. Further evaluation of 13 C‐breath test in general would be worthwhile. The LiMAx test as a 13 C‐breath test accessing liver function might be of particular predictive interest if patients with ECMO therapy develop multiorgan failure.